Mathematical Literacy teachers: Can anyone be one? - Hanlie Botha; Jacobus Maree; Gerrit Stols (Perspectives in Education, 2013)
In this case study, Mathematical Literacy teachers were interviewed and observed in the classroom in order to provide insight into the way this subject, relatively new in South African schools, is handled. The focus of this research was the instructional practice of these teachers specifically in terms of their mathematical knowledge regarding the subject and its learners. The idea that this subject is inferior to other subjects in general, but to mathematics in particular, was alluded to by some participants, alongside of the notion that it was infra dig to teach it. The study revealed that a working knowledge of mathematics as well as teaching-and-learning skills are necessary for this subject to achieve what it was meant to do when it was introduced into South African high schools in 2006.